Laparoscopic management of gastric gastrointestinal stromal tumors (2014)
ABSTRACT: Gastrointestinal stromal tumors (GISTs) are the most frequent gastrointestinal tumors of mesodermal origin. Gastric GISTs represent approximately 70% of all gastrointestinal GISTs. The only curative option is surgical resection. Many surgical groups have shown good results with the laparoscopic approach. There have not been any randomized controlled trials comparing the open vs laparoscopic approach, and all recommendations have been based on observational studies. The experience obtained from gastric laparoscopic surgery during recent decades and the development of specific devices have allowed the treatment of most gastric GISTs through the laparoscopic approach.